Analisis Faktor yang Mempengaruhi Kondisi Rumah Masyarakat Desa Helandohi Menggunakan Analisis Regresi Berganda - Jeni Marianti Loban; Jefrianus Mau (Program Studi Matematika Universitas Negeri Jakarta, 2023)
This study aims to see the relationship between the Dependent Variable (Y), namely the condition of the house, Independent Variable (X1): number of family members, Independent Variable (X2) : education level, and Independent Variable (X3): family income. The data was obtained directly (primary data). Using multiple linear regression method with SPSS software. The result obtained from the F test the variable number of family members (X1), the education level variable (X2), and the family income variable (X3) simultaneously influence the housing condition variable. The regression equation is Y = 0.398 + 0.019 X1 + 0.001 X2 – 0.019X3 and the value of R2 = 0.76.